GAMBARAN MOTIVASI WUS UNTUK MENGIKUTI PEMERIKSAAN PAP SMEAR DI KELURAHAN PRAJURIT KULON KECAMATAN PRAJURIT KULON KOTA MOJOKERTO - Dewi Yanti, Ariu (JURNAL KEPERAWATAN SEHAT, 2012)
Motivation means a stimulus in human beings to act or behave. Motivation is influenced by several factors: age, education, information and employment status. The purpose of this reseach to know the description of motivation of Eligible woman to follow the Pap Smear inspection . This reseach used a descriptive design. The reseach was conducted on April 29, 2012. The population is all Eligible women who are married in kelurahan Prajurit Kulon RT 01 RW 04 Kecamatan Praurit Kulon Kota Mojokerto numbered in 41 people, while the sample numbered in 21 peope with sample taken using purposive sampling techniques. The variables in this reseach is single, that is Motivation of Eligible woman to follow Pap Smear inspection in Kelurahan Prajurit Kulon RT 01 RW 04 Kecamatan Prajurit Kulon Kota Mojokerto. Data collection techniques using questionnaires. The results show the motivation of eligible women to follow the Pap Smear inspection in Kelurahan Prajurit Kulon RT 01 RW 04 Kecamatan Prajurit Kulon Kota Mojokerto are classified as moderate, it can be seen from the 21 respondents there were 2 people (9.52%) have high motivation, 17 people ( 80.95%) are moderate motivated and 2 (9.52%) have low motivation. Motivation is affected by age because the maturity level of age are more mature a person would think more mature, if the level education is higher usually have a wider vision, a person who has a job will have enough income to fulfill necessities of their life and are motivated following Pap Smear inspection , the more information is obtained about the Pap smear is more higher motivation to follow the Pap Smear.Key words: motivation, Eligible woman, Pap Smear